The Effect of Educational Strategies Targeted for Nurses on Pain Assessment and Management in Children: An Integrative Review - Kusi Amponsah A.; Björn A.; Bam V.; Axelin A. (W.B. Saunders, 2022)
Background: Nurses play an important role in children's pain assessment and management because they spend the majority of the time with them and provide care on a 24-hour basis. However, research studies continue to report on nurses' inadequate assessment and management of children's pain, which may be partly attributed to their insufficient education in this area.
Objectives: This integrative review sought to examine the effect of strategies used in educating nurses on pediatric pain assessment and management.
Design: An integrative review.
Data Sources: Cumulative Index to Nursing and Allied Health Literature, Cochrane, PubMed/ Medline and Scopus.
Review/Analysis Methods: Four databases were searched up to February 2018 based on a prescribed eligibility criteria. The review included 37 studies with varied methodologic quality.
Results: Our findings revealed that various types of educational strategies improve nurses’ knowledge, attitudes, and practice of pain assessment, management, and/or documentation.
Conclusions: Developing a responsive program that includes expectations of beneficiaries, integrating it into existing facility training systems and delivering it through multidisciplinary collaboration, offers the benefit of securing sustainability of the educational gains.